Prevalence of psychological stress among undergraduate students attending a health programme in a Malaysian University - Phang, Cheng Kar; Mohd Sidik, Sherina; Jamil @ Osman, Zubaidah; Naing, Khin Ohnmar@Noor Jan; Mukhtar, Firdaus; Ismail, Siti Irma Fadhilah; Ibrahim, Normala (Universiti Putra Malaysia Press, 2015)
Psychological stress among undergraduate students is associated with poor academic results, physical ill-health and psychiatric disorders. The objectives of the study were to determine the prevalence of psychological stress and its associated factors among undergraduate students attending a health programme in a local university. This is a cross-sectional study among undergraduate students attending a health programme in a local university. The 12-item General Health Questionnaire (GHQ-12) was used to determine the presence of psychological stress at a cut-off point of 4 and above. Analysis was conducted to determine any association between gender, ethnicity, year of study in the university, recent health-seeking contact with a doctor, and psychological stress among the participants. The prevalence of psychological stress among undergraduate students attending a health program in a Malaysian University was 49.3%. There was no significant association with any of the socio-demographic factors studied (p>0.05). The prevalence of psychological stress in this study was significantly high, and irrespective of gender, ethnicity, year of study in the university, and recent health-seeking contact with a doctor. Hence, the findings of this study show that it may be a useful strategy to integrate such health programs regularly in activities of colleges and universities, with the aim of promoting mental health and wellness among the students.